2015
DOI: 10.1002/joc.4210
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing for climate and atmospheric sciences: current status and future potential

Abstract: Crowdsourcing is traditionally defined as obtaining data or information by enlisting the services of a (potentially large) number of people. However, due to recent innovations, this definition can now be expanded to include ‘and/or from a range of public sensors, typically connected via the Internet.’ A large and increasing amount of data is now being obtained from a huge variety of non‐traditional sources – from smart phone sensors to amateur weather stations to canvassing members of the public. Some discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
266
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(270 citation statements)
references
References 100 publications
2
266
0
2
Order By: Relevance
“…Figure 6 aims only to provide a simple generalization of the situation. There are, for example, a wide variety of weather related citizen science projects which could occupy different locations in the space depicted in Figure 6; see for example, [56].…”
Section: Nature and Types Of Crowdsourced Geographic Informationmentioning
confidence: 99%
“…Figure 6 aims only to provide a simple generalization of the situation. There are, for example, a wide variety of weather related citizen science projects which could occupy different locations in the space depicted in Figure 6; see for example, [56].…”
Section: Nature and Types Of Crowdsourced Geographic Informationmentioning
confidence: 99%
“…Data quality is reported to increase with the number of contributions (e.g., as 442 cited in Muller et al, 2015), and it is even reported that high quality data can emerge from a vast 443 amount of low quality data (De Longueville, 2015). It does not mean that more contributions 444 automatically result in better quality outputs, but rather that more contributions allow for a stronger 445 quality check of the crowdsourced data.…”
mentioning
confidence: 99%
“…458 However, crowdsourcing approaches based on more flexible data models have shown a greater 459 potential to 1) support unanticipated evolution of the crowdsourcing initiatives and 2) attract and 460 maintain a larger group of contributors (Lukyanenko et al, 2014 (Muller et al, 2015).…”
mentioning
confidence: 99%
“…CML technology has recently been mentioned as one of the first Internet of Things (IoT) applications [85], which is now getting much attention. While the conditions for CML technology becoming useful seems to be right, and we may see it soon in products as well as in public-good services, it also serves as a pioneering example of the new trend of capitalizing on existing technology by utilizing it for non-intended, opportunistic use [86][87][88].…”
Section: A Test Case For Opportunistic Sensing Of the Environmentmentioning
confidence: 99%